The gender division of labor and second births: Labor market institutions and fertility in Japan - Nobuko Nagase; Mary C. Brinton (Demographic Research, 2017)
Background: Research has examined how the gendered household division of labor may deter the transition to second birth. However, little research has investigated how workplace norms influence men's household work. Objective: This paper takes into account labor market structure, workplace norms, and the legal environment governing working conditions to contextualize men's contribution to household labor and its effect on transition to second birth. Methods: Using data from the Japanese Longitudinal Survey of Adults in the 21st Century (2002 Cohort), we employ fixed-effects models to estimate the effect of workplace norms on men's contribution to household work and the effect of men's household work hours on transition to second birth. Results: Japanese male university graduates in large firms do a smaller share of household labor than other men. These men are subject to workplace norms prevalent in firm-internal labor markets, which have been supported by Japanese Supreme Court rulings. These norms influence men's allocation of time between the workplace and the home. Moreover, analysis of the transition to second birth indicates that husband's share of household work is an important predictor of second birth, especially for dual-earner couples. Conclusions: Our empirical results suggest that unless changes are made in Japanese employment law and workplace norms, dual-earner couples in particular will continue to face difficulties proceeding to a second birth. Contribution: This paper demonstrates how the economic and cultural context can create disincentives for men to contribute to household labor, which in turn lowers the probability of transition to second birth.